Physiological Metabolic Responses of Ophraella communa to High Temperature Stress - Chen, Hongsong; Solangi, Ghulam Sarwar; Zhao, Chenchen; Yang, Lang; Guo, Jianying; Wan, Fanghao; Zhou, Zhongshi (Frontiers in Physiology, 2019)
Considering the predicted rising temperatures under current climate change and heat waves scenarios, organisms are expected to suffer more intense and more frequent thermal stress. Induced heat is accumulated by organisms and can cause a variety of physiological stress responses. Ophraella communa is a known effective biological control agent of common ragweed, Ambrosia artemisiifolia, but the responses of this agent to heat stress have not been fully elucidated and, therefore, its potential responses to climate change are uncertain. We investigated the physiological metabolism of subsequent O. communa adults after: (1) different developmental stages (egg, larval, pupal, and adult) were exposed to thermal stress for 3 h each day for 3, 5, 5, and 5 days, respectively (by stage); and (2) individuals were exposed to thermal stress throughout the egg-to-adult period for 3 h each day. High temperatures of 40, 42, and 44°C were used to induce thermal stress. A control group was reared at 28 ± 2°C. The results showed that short- or long-term exposure to daily phasic high temperatures significantly decreased water and lipid contents and significantly increased glycogen and glycerol contents in all adults (i.e., after exposure of different stages or throughout the egg-to-adult period). The total sugar content increased significantly in adults after the eggs and larvae were exposed to brief short-term thermal stress. Compared to the control, the total sugar content was also significantly higher in the adults and pupae exposed to 44°C. Total sugar content in females increased significantly in response to long-term phasic thermal stress at 40°C. However, sugar content of males exposed to 44°C decreased significantly. Stage-specific responses were observed. After long-term phasic thermal stress, water and glycogen contents in males were significantly higher than the females; however, females had higher total sugar and lipid contents. Significant differences were detected in glycerol contents of females and males. Our study provides a basic understanding of the metabolic responses of O. communa to thermal stress and offers insights into its potential as a natural biocontrol agent against A. artemisiifolia during the summer season and under predicted climate change scenarios.